English Language Learners’ Perspectives On Implementing Gpts For Learning Purposes In The Context Of Ai Literacy-focused Pedagogical And Assessment Approach - Makinina, Olga; Carra-Salsberg, Fernanda (The Journal of Studies in Language, Culture, and Society, 2025)
As AI-powered chatbots become prevalent in academia, there is a need for research practitioners working with English language learners (ELLs) to examine how students use generative AI (GenAI) for learning purposes. Teachers and researchers express concern with the potential detrimental impact of GenAI on ELLs’ intellectual engagement with learning (e.g., Barrot, 2023; Cardon et al., 2023; Cong-Lem et al., 2024). Meanwhile, emerging research highlights that for language educators, it is essential to evolve with technological advancements and - instead of attempting to avoid the unavoidable use of GenAI - apply such tools to promote sustained learning (Bui & Tong, 2025; Warschauer et al., 2023; Yeo, 2023).This article reports on a study in an English for Academic Purposes (EAP) course that incorporated ChatGPT into scaffolded assessment practices. The study explored students’ experiences using ChatGPT to brainstorm and revise their writing while immersed in AI literacy-focused instruction. Its post-instruction survey findings demonstrate that although students perceive GenAI as a tool to adapt to their learning needs, thereby enhancing language skills, they also recognize GenAI limitations (e.g., inaccurate output) and share concerns that are common among educators (e.g., overdependency on AI tools and breaching academic integrity). The implications suggest that when used responsibly, GenAI can supplement rather than replace students’ work. Educators might benefit from adopting a pedagogical and assessment framework focused on critical thinking, creativity, and digital literacy skills. Such approach fosters active learning through scaffolded formative assessments targeted at deconstructing, evaluating, and consciously incorporating GenAI-generated text into one’s writing.